Toward an integrated sustainability assessment in through-life engineering services - Farsi, Maryam; Erkoyuncu, John Ahmet (Elsevier, 2020)
Through-life Engineering Services (TES) is comprised of develop, prepare, utilize and retire phases for complex engineering assets with a focus on maximizing their availability, predictability and reliability at the lowest possible life-cycle cost. TES employs a set of technologies and solutions to improve asset performance efficiently. On the other hand, optimal solutions for minimizing waste in terms of service time and resources is crucial for designing the right service at the right time. Thereby, specifying the possible TES opportunities within the economic, social and environmental sustainability dimensions can be an added value across different manufacturing sectors when deploying TES. However, due to the complexities and immensity of TES approaches, it is challenging to perceive such opportunities. To this end, the existing literature is limited to the effect of TES on economic sustainability and mostly focuses on investigating how TES has modified the service design to improve productivity and profitability. However, a comprehensive study on integrated sustainability has not been yet conducted. This paper presents a holistic view of the potential TES opportunities associated with the sustainability triple bottom line following a systematic review of empirical and theoretical advancements and methodological approaches in the literature. The outcome from this research raises the awareness of TES contribution in the design of sustainable service solutions and technologies, and offers a benchmark and reference point for future research in the field. Finally, this paper provides a set of recommendations that call for the further development of an integrated sustainability assessment framework for TES.
Keywords: Through-life Engineering Services (TES); Sustainability; Product life-cycle; Integrated Sustainability Assessment; Sustainable development; Systematic Review